2018
DOI: 10.1093/infdis/jiy637
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Efficacy of Artemether-Lumefantrine and Dihydroartemisinin-Piperaquine for the Treatment of Uncomplicated Malaria in Ugandan Children

Abstract: Background In Uganda, artemether-lumefantrine (AL) and dihydroartemisinin-piperaquine (DHA-PQ) showed excellent treatment efficacy for uncomplicated malaria in prior trials. Because the frequency of resistance to artemisinins and piperaquine is increasing in Southeast Asia and the prevalence of Plasmodium falciparum polymorphisms associated with resistance has changed, we reassessed treatment efficacies at 3 sites in Uganda. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

5
25
2

Year Published

2019
2019
2021
2021

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 36 publications
(32 citation statements)
references
References 29 publications
5
25
2
Order By: Relevance
“…In Tororo, this regimen was widely used in different drug trials for malaria treatment [47,48] and chemoprevention [24,[49][50][51][52]. Previous studies indicated that dihydroartemisinin-piperaquine treatment selected the N86Y allele in pfmdr1 in Uganda [48,[52][53][54], albeit one study questioned this association [55]. Approximately one third of parasites possessed the N86Y in 2010-2013 in Tororo [9], which was much higher than that found in our study area (2%).…”
Section: Discussioncontrasting
confidence: 60%
“…In Tororo, this regimen was widely used in different drug trials for malaria treatment [47,48] and chemoprevention [24,[49][50][51][52]. Previous studies indicated that dihydroartemisinin-piperaquine treatment selected the N86Y allele in pfmdr1 in Uganda [48,[52][53][54], albeit one study questioned this association [55]. Approximately one third of parasites possessed the N86Y in 2010-2013 in Tororo [9], which was much higher than that found in our study area (2%).…”
Section: Discussioncontrasting
confidence: 60%
“…In Tororo, this regimen was widely used in different drug trials for malaria treatment [47,48] and chemoprevention [24,[49][50][51][52]. Previous studies indicated that dihydroartemisinin-piperaquine treatment selected the N86Y allele in pfmdr1 in Uganda [48,[52][53][54], albeit one study questioned this association [55]. Approximately one-third of parasites possessed the N86Y in 2010-2013 in Tororo [9], which was much higher than that found in the studied area (2%).…”
Section: Discussionmentioning
confidence: 84%
“…AL, the most commonly recommended ACT medicine in malaria-endemic countries, remains highly efficacious in Africa, despite its use as first-line treatment of uncomplicated falciparum malaria for more than a decade [2541]. DHA/PPQ has recently been adopted as second-line treatment in several malaria-endemic countries in the African and Eastern Mediterranean regions, and the available data show high efficacy [25, 27, 30, 3437, 39, 41, 42]. This high efficacy may be explained by the recent introduction of DHA/PPQ as second-line treatment, suggesting weak drug pressure through its limited use.…”
Section: Discussionmentioning
confidence: 99%